Improving Speaking Ability Using Role Play For The Students Of Fifth Grade Of SD Negeri 02 Brangkal Gemolong Sragen In 2010/2011 Academic Year - Ningtyas, Retno Sari (2012)
The objective of this action research was to improve students speaking ability using role play at the fifth grade of SD Brangkal 02 Gemolong Sragen by the process of planning and reflecting collaborative efforts. The data were collected through observing the teaching learning taking place, interview, and speaking test. The researcher applied role play. There are three states in role play. The first is pre-speaking, while-speaking and postspeaking. In this research, the researcher modified those stages by putting languange expression. The researcher grouped the students into small groups. The result of cycle 1 shows that the students were able to pronounce the words well, they started to use expressing preference and gambits, which was introduced by the researcher. Some students tried to ask and answer the simple question, but they still found difficulties in producing language expression and some of them still passive when speaking English in the cycle II, the researcher repeat language expression. The researcher divided the students in group. The research used and apply role play again by inserting practicing role play. The result of cycle II was that the students speaking ability improvees. The students were more active, most of them practiced some language expression and they practice to make sentence in English. They looked more confident when speaking English. Their vocabulary improves. The students could pronounce the words well.